Do Migrants Lower Workplace Wages? - Michael White; Alex Bryson (Institute of Labor Economics (IZA), 2017)
Using nationally representative workplace data for Britain we identify the partial correlation between workplace wages and the percentage of migrants employed at a workplace. We find wages are lower in workplaces employing a higher percentage of migrants, but only when those migrants are non-EEA migrants. However, the effects are no longer apparent when we condition on the ethnic complexion of employees at the workplace. Instead, the wage penalty is attached to the percentage of non-white employees, a finding that is consistent with employer discrimination on grounds of race, or lower worker bargaining power when employees are ethnically diverse.
Keywords: J31; J61; J71; 330; migrants; migration; ethnicity; race; wages; earnings; low pay; discrimination